2018
DOI: 10.1080/13811118.2018.1501448
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Adolescents’ Experiences of Self-Harm: Secondary Analysis of Family Therapy Sessions from the SHIFT Trial

Abstract: The objective of this study was to explore, using first-hand accounts, adolescents' understandings of why they self-harmed, what their responses to self-harm were, and how they resisted or ceased self-harm. Secondary analysis was conducted of video-recorded family therapy sessions from the Self-harm Intervention: Family Therapy (SHIFT Trial). Recordings of 22 participants, approximately 170 hours of footage, formed the dataset. The study developed 5 core themes: (1) Distress can be difficult to convey; (2) Sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…They recommended mental health professionals to ask for feedback to increase helpful interventions. Adolescents also describe ending self-harm by managing and communicating difficult affect and distress to their family (Holliday, Brennan, & Cottrell, 2018).…”
Section: Qualitative Studies On Adolescents' Experience Of Self-harmmentioning
confidence: 99%
“…They recommended mental health professionals to ask for feedback to increase helpful interventions. Adolescents also describe ending self-harm by managing and communicating difficult affect and distress to their family (Holliday, Brennan, & Cottrell, 2018).…”
Section: Qualitative Studies On Adolescents' Experience Of Self-harmmentioning
confidence: 99%
“…Meanwhile, while the participants per Ammerman et al’s ( 2017 ) definition quantitatively reported clinically significant levels of NSSI in adolescence, little significance was attributed to self-injury per se . NSSI was narratively situated as one method among others to manage contextual stressors, and not something intended for communicating distress to others (e.g., Holliday et al, 2018 ) or as causing distress in itself (e.g., Brown & Kimball, 2013 ). This implies that in the current study, NSSI was neither the source nor a symptom of their issues, meaning that discontinuing NSSI within this context was a change in endurance strategy rather than indicative of greater psychological well-being or improved life circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…This might be particularly important because all participants who had sought counselling said it had been unhelpful prior to their turning point, and narratives about difficulties in engaging in healthcare are commonly reported by individuals who self-injure (Lindgren et al, 2018 ). Moreover, youth who are self-injuring also commonly report unique difficulties concerning ambivalence, honesty, engaging with difficulties beyond the therapy sessions, and decisions to keep up a façade and manage alone (Holliday et al, 2018 ). Furthermore, in accordance with Kelada et al ( 2018 ), tensions and mistrust may be narrated when individuals perceive healthcare professionals to be focused more on their behaviours (e.g., self-injury) or symptoms (e.g., depressive symptoms) rather than on their context, or as our participants noted, they had a need to talk about what had happened to them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key advantage is the possibility to develop theories beyond those established in individual studies and thus, identify any knowledge gaps (Walsh & Downe, 2006). Further, qualitative evidence more accurately elucidates individual experience, offering a unique insight for improving service provision and tailoring therapeutic interventions more accurately to patient need (Holliday et al, 2020).…”
Section: Methodsmentioning
confidence: 99%